2021
DOI: 10.3390/ma14030655
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Heavy Metal Ions from Wastewaters: An Application of Sodium Trithiocarbonate and Wastewater Toxicity Assessment

Abstract: The synthesis and application of sodium trithiocarbonate (Na2CS3) for the treatment of real galvanic wastewater in order to remove heavy metals (Cu, Cd and Zn) was investigated. A Central Composite Design/Response Surface Methodology (CCD/RSM) was employed to optimize the removal of heavy metals from industrial wastewater. Adequacy of approximated data was verified using Analysis of Variance (ANOVA). The calculated coefficients of determination (R2 and R2adj) were 0.9119 and 0.8532, respectively. Application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Na 2 CS 3 has been reported as an effective precipitating agent to remove heavy metals from galvanic wastewater for decades. 40,41 Trithiocarbonates can be easily formed from a reaction between carbon disulde (CS 2 ) and other sulde sources. [42][43][44] Here, the synthesis of Na 2 CS 3 was carried out by a one-step wet ball milling of sodium sulde (Na 2 S), and an excess amount of CS 2 in a mole ratio of 1 : 3.…”
Section: Synthesis and Materials Characterizationmentioning
confidence: 99%
“…Na 2 CS 3 has been reported as an effective precipitating agent to remove heavy metals from galvanic wastewater for decades. 40,41 Trithiocarbonates can be easily formed from a reaction between carbon disulde (CS 2 ) and other sulde sources. [42][43][44] Here, the synthesis of Na 2 CS 3 was carried out by a one-step wet ball milling of sodium sulde (Na 2 S), and an excess amount of CS 2 in a mole ratio of 1 : 3.…”
Section: Synthesis and Materials Characterizationmentioning
confidence: 99%
“…The metal hydroxides that are inexplicable in the alkaline medium are increased when the pH is changed. For metal(loid)s removal, layered double hydroxides are produced in the case of trivalent ions (Thomas et al, 2021). To create a hydroxide precipitate, several precipitants such as lime, calcium hydroxide, ammonium hydroxide, and sodium hydroxide are presented.…”
Section: Hydroxide Precipitationmentioning
confidence: 99%
“…Recent studies have shown that polluted waters or industrial wastewaters may contain varying amounts of zinc, for example, 52.8 mg/L (electroplating company, Atom, Dubna, Russia) [ 14 ], 10 mg/L, being approximately 80% and 20% in the form of Zn 2+ and ZnSO 4 (aq), respectively [ 15 ], 33.3 g/L (spent acid solution from the pickling stage of a galvanizing plant) [ 16 ], 1392.1 mg/L (zinc plating industry) [ 17 ], 22.7 mg/L (galvanic wastewater) [ 18 ] and 49.8 mg/L (zinc electroplating industry) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It consists of the use of alkaline reagents (NaOH, CaO, Ca(OH) 2 and Na 2 CO 3 ) for the precipitation of sparingly soluble metal hydroxides in which its solubility depends on the pH of the wastewater. However, this method has some limitations, i.e., using high doses of alkaline reagents, large volumes of sludge and limited effectiveness in the case of amphoteric hydroxides and in the presence of complexing compounds [ 18 , 26 , 27 , 28 , 29 , 30 , 31 ]. In these cases, additional precipitants are used to ensure that the concentration of metals in the wastewater treatment is reduced to the legal requirements.…”
Section: Introductionmentioning
confidence: 99%